Diet composition and feeding strategy of crossbanded barb, Puntioplites bulu (Bleeker, 1851) in Perak River, Peninsular Malaysia - A Ghani, Intan Faraha; Arshad, Aziz; Harmin, Sharr Azni; Christianus, Annie; Ismail, Muhammad Fadhil Syukri (Triveni Enterprises, 2020)
Aim: The present study deals with the diet composition and feeding strategy of P.bulu from Perak River, Peninsular Malaysia in relation to its development stage and size. Methodology: Diet composition and feeding strategy of crossbanded barb, P. bulu captured from Perak, Peninsular Malaysia were studied between October 2015 and September 2016. Diet compositions were determined through a microscopic examination and feeding items were identified to the lowest taxonomic level possible. The feeding strategy for both stages (adult and juvenile) were determined based on Amundsen graphical method. Results: Findings of this study revealed that this species is a planktivorous species that feeds primarily on Bacillariophyceae. Based on Simple Resultant Index, there are seven major diet items groups consumed by P.bulu in the population. Ontogenetic dietary shifts were perceived to be stage related, with adult stages consuming larger-sized prey while juveniles were predominantly herbivorous and fed primarily on smaller dietary items. Interpretation: Puntioplites bulu inhabiting Perak River is planktivorous. This species demonstrated mixed feeding strategy and ontogenetic dietary changes was observed between juvenile and adult stages.